Identifikasi Infeksi WSSV (White Spot Syndrome Virus) Pada Udang Vaname (Litopaneus vannamei) Dengan Metode PCR (Polimarace Chain Reaction) Di Kecamatan Wanggarasi - Abudi, Candra Perdana; Koniyo, Yuniarti; Suherman, Sutianto Pratama; Lamadi, Arafi (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to identify White Spot Syndrome Virus (WSSV) infection in vannamei shrimp ponds cultivated in Wanggarasi Sub-district, Pohuwato Regency, using the Polymerase Chain Reaction (PCR) test method. The method applies descriptive analysis method, observation method, and laboratory analysis. The results showed that after being detected by PCR from 4 sampling stations, stations 3 was detected positive (+) for moderate virus infection at stations 1, 2, and 4. The results of identification using the PCR (Polymerase Chain Reaction) method at the Fish Quarantine Station and Quality Assurance of Gorontalo Province, the white spot syndrome virus (WSSV) was not detected in vannamei shrimp, or negative (-) with clinical symtomps, namely; pale color, slow movement, leaning against the embankment, there is a light spot on the head, swimming on the surface.